Oxygen diffusion and edema with modern scleral rigid gas permeable contact lenses - Compañ-Moreno, V. (2014)
PURPOSE. We defined the theoretical oxygen tension behind modern scleral contact lenses (CLs) made of different rigid gas permeable (RGP) materials, assuming different thickness of the tear layer behind the lens. A second goal was to show clinically the effect of the postlens tear film on corneal swelling. METHODS. We simulated the partial pressure of oxygen across the cornea behind scleral CLs made of different lens materials (oxygen permeability Dk, 75–200 barrer) and different thickness (Tav, 100–300 lm). Postlens tear film thicknesses (Tpost-tear) ranging from 150 to 350 lm were considered. Eight healthy subjects were fitted randomly with a scleral lens with a thin and a thick postlens tear layer in two different sessions for a period of 3 hours under open-eye conditions. RESULTS. The CLs with less than 125 barrer of Dk and a thickness over 200 lm depleted the oxygen availability at the lens–cornea interface below 55 mm Hg for a postlens tear film of 150 lm. For a postlens tear film thickness of 350 lm, no combination of material or lens thickness will meet the criteria of 55 mm Hg. Our clinical measures of corneal edema showed that this was significantly higher (P < 0.001, Wilcoxon signed ranks test) with the thicker compared to the thinner Tpost-tear (mean 6 SD, 1.66 6 1.12 vs. 4.27 6 1.19%). CONCLUSIONS. Scleral RGP CLs must be comprised of at least 125 barrer of oxygen permeability and up to 200 lm thick to avoid hypoxic effects even under open eye conditions. Postlens tear film layer should be below 150 lm to avoid clinically significant edema